Higher Serum Uric Acid is a Risk Factor of Reduced Muscle Mass in Men with Type 2 Diabetes Mellitus - Tanaka, Ken-ichiro; Kanazawa, Ippei; Notsu, Masakazu; Sugimoto, Toshitsugu (Experimental and Clinical Endocrinology & Diabetes, 2018)
Objective Sarcopenia has been recognized as a diabetic complication, and hyperuricemia is often accompanied by type 2 diabetes mellitus (T2DM). However, it is unknown whether serum uric acid (UA) levels are associated with reduced muscle mass in T2DM.Methods We conducted a cross-sectional study to investigate the association of serum UA with muscle mass in 401 subjects with T2DM (209 men and 192 postmenopausal women). The relative skeletal muscle mass index (RSMI) was evaluated using whole-body dual-energy x-ray absorptiometry.Results Multiple regression analyses adjusted for body weight, age, serum creatinine, hemoglobin A1c (HbA1c), and duration of T2DM showed that serum UA was negatively associated with RSMI in all subjects and men with T2DM (β=−0.13, p=0.001 and β=−0.17, p=0.003, respectively). Moreover, logistic regression analyses adjusted for these confounding factors showed that a higher serum UA level was significantly associated with low RSMI in men with T2DM [odds ratio (OR)=1.94, 95% confidence interval (CI)=1.10–3.45 per SD increase, p=0.023]. In addition, higher serum UA levels were significantly associated with low RSMI after additional adjustment for age, duration of T2DM, HbA1c level, serum creatinine level, and sex in all subjects with T2DM [OR=1.80, 95% CI=1.20–2.72 per SD increase, p=0.005].Conclusions The present study showed for the first time that higher serum UA is an independent risk factor of reduced muscle mass in men with T2DM.
Keywords: uric acid; hyperuricemia; muscle mass; sarcopenia; diabetes mellitus